Aberrant DNA hypermethylation of the ITIH5 tumor suppressor gene in acute myeloid leukemia - Oing, Christoph (Springer-Verlag, 2011)
Epigenetic mechanisms such as DNA hypermethylation and modifications of histone amino acids are known to play an important role in the control of gene expression both in normal human development and tumorigenesis. Hypermethylation of CpG islands within promoter regions of tumor suppressor genes is associated with transcriptional inactivation and represents, in addition to genetic aberrations, an important mechanism of gene silencing in the pathogenesis of human cancer. Inter-α-trypsine inhibitors (ITIs) are a family of serine protease inhibitors consisting of one light chain (bikunin) and two heavy chains (ITI heavy chains, ITIHs). ITIHs stabilize the extracellular matrix (ECM) by interacting with hyaluronic acid, which is a major ECM component. Hypermethylation in the upstream region of the promoter-associated CpG island of ITIH5, the most recently described member of the ITIH family, has been previously detected in breast cancer and was associated with an adverse outcome. In this study, we determined the DNA methylation status of the promoter region near the transcription start site of the ITIH5 tumor suppressor gene in leukemia cell lines and primary samples from patients with acute myeloid leukemia (AML) as well as the potential use of demethylating agents to restore a demethylated state of the promoter. Aberrant ITIH5 promoter hypermethylation occurred in 15 of 104 (14.4%) diagnostic AML samples. There were no statistically significant correlations between the ITIH5 methylation status and clinical prognostic parameters. Our results indicate that aberrant ITIH5 promoter hypermethylation is a novel epigenetic event in AML.